A formação para as relações etnicorraciais e a profissionalização em história: saberes e práticas docentes no contexto da educação a distância - Ferreira, Maria Cláudia Cardoso (2013)
The present work researched the experience of graduation in History by distance teaching modality. The secular teachers acting in basic education, chosen for Pro-Licenciatura II Program and working in Bahia, Maranhão, Sergipe and Ceará were the subject of this research. The Pro-Licenciatura II Program was funded by Ministry of Education through a partneship between Pontifícia Rio de Janeiro University and State University of Rio de Janeiro, by 2006 until 2010. The subject of this estudy was the applicability of the Law 11.645/08, that it was 10.639/03. This Law changed the Directives and Educations Bases Law 9.394/03, by introducing the compulsory study of afro-Brazilian and indigenous history and culture establishments in all elementary and middle schools, public and private of the country. There are interesting studies which relates educations and ethinic racial relations. However, there are few studies about initial or continued education of teachers. Focusing the superior education institutes as a place that needs to be investigated and understand how the History Courses has been organized to follow the law are challenges. Which disciplines are ofered? How are ethno racial relations theme in the curriculum of the courses? How undergraduates and professsors work with the obligatoriness of that law? How the prodution and mobilizations of diferents knowledges, and also the practices about that themes works? The question of the level teacher´s compromise with this theme guided this research. The answer for all that issues was guided by contributions of Maurice Tardif about the knowledge of professors based on case study metodology. This metodology use interviews, forms, analyses of papers for de classes made by teachers, the online atmosphere of the class and the oficial documents that organized the class and instituted that law. The investigation revealed the teachers effort for knowlodge and practices about the themes of the law. On the other hand, some elements put limit on the profissionalization, as exemple, the study by distance format, the ignorance about the theme and the disponibility of the teacher apprentices.